La Société d’étude du féodalisme : documents, témoignages, perspectives - Solal Abélès (L'Atelier du CRH)
The Société d’étude du féodalisme, founded in 1975, was, if not legally dissolved, at least definitively put to sleep no later than 1983. Although it is hardly mentioned in contemporary scientific literature, hardly mentioned later by those who frequented it and consequently almost forgotten today, it nevertheless constituted one of the most fertile places of intellectual exchange of its time by attracting several dozen regular participants, medievalists and modernists for the most part. By relying on the documents produced within it and now constituted in the archives, as well as on a series of retrospective testimonies of five of its principal members, the present article aims to lay down the milestones of the history of the society that produced them and to open up some avenues of reflection based on the research practices to which it bears witness.